2020
DOI: 10.21203/rs.3.rs-32388/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccination concerns, beliefs and practices among Ukrainian migrants in Poland: A qualitative study

Abstract: Background: Ukrainians numbering approximately 1.2 million are the largest migrant group in Poland. Data on vaccination coverage among migrants are not collected in EU, including Poland. Therefore, this qualitative study aimed to identify vaccination practices in this migrant group, to explore facilitators and barriers to vaccination and related access to Polish healthcare services.Methods: In September 2019, a qualitative study of Ukrainian migrants (UMs) living in Szczecin, Poland, and recruited through a sn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…(35,52) In the absence of translated or accessible information, many migrants reported that they turned to alternative and unregulated sources, such as Google, social media, friends, and family. (22,33,53,56,57) ii. Practical and legal barriers to accessing healthcare and services Practical and legal barriers to accessing healthcare (whether perceived or real) and vaccination delivery models, meant that many migrants experienced exclusion and challenges accessing vaccination services.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
See 4 more Smart Citations
“…(35,52) In the absence of translated or accessible information, many migrants reported that they turned to alternative and unregulated sources, such as Google, social media, friends, and family. (22,33,53,56,57) ii. Practical and legal barriers to accessing healthcare and services Practical and legal barriers to accessing healthcare (whether perceived or real) and vaccination delivery models, meant that many migrants experienced exclusion and challenges accessing vaccination services.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
“…(31,36,65) Fears of being charged for care or asked about immigration status, distrust of HCPs and authorities based on rumours or past experiences of discrimination, difficulties registering with a GP, or being refused care, were also highlighted. (7,31,36,(55)(56)(57)65) These fears were a major barrier to COVID-19 vaccination access in two UK studies of asylum seekers, refugees, and migrants with precarious immigration status, who expressed concern that they would be de-prioritised or excluded from the COVID-19 vaccine roll-out because of their status. (7,56) Migrants (n=10) interviewed after government announcements to widen COVID-19 vaccine access to undocumented migrants also remained unaware that they could be accessed free of charge and without immigration checks.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
See 3 more Smart Citations